Mobile Tracking Based on Support Vector Regressors Ensemble and Game Theory. (11th March 2014) - Zeng, Fanzi; Liu, Shaoyuan; Li, Renfa; Zeng, Qingguang
Abstract : A two-step tracking strategy is proposed to mitigate the adverse effect of non-line-of-sight (NLOS) propagation to the mobile node tracking. This strategy firstly uses support vector regressors ensemble (SVRM) to establish the mapping of node position to radio parameters by supervising learning. Then by modelling the noise as the adversary of position estimator, a game between position estimator and noise is constructed. After that the position estimation from SVRM is smoothed by game theory. Simulations show that the proposed strategy results in the more accurate performance, especially in the harsh environment.